Representation of The Development of Marijuana Legalization In The Frame f Online Media Coverage Tempo.com And Kompas.com - Radja Juan Poda Pasaribu; Syukur Kholil (LEGAL BRIEF, 2022)
This study aims to determine the representation of the development of marijuana legalization in the frame of online media coverage tempo.co and Kompas.com. As a theoretical basis in analyzingproblems in research are theories of representation of development, marijuana, media and news. This research uses a qualitative approach that is descriptive. The source of the data is from primary data and secondary data, and the primary is all news about the legality of cannabis that researchers analyze in the tempo.co and kompas.com media that researchers choose . The secondary data are books and journals related to the study. The techniques that researchers use are library analysis, observation, and documentation on the legalization news that has been selected. Researchers use phenomenological studies, where researchers look for the meaning of the phenomenon in the news of marijuana legalization that researchers have chosen. The data analysis used by researchers is descriptive data analysis, which is to summarize all data generated from analyzing the activities of analyzing berries using the technique of validity of triangulation data, namely checking the data that has been obtained from all informants, there are 3 types of triangulation or penge Cekan is source triangulation, data collection technique triangulation, and time triangulation. The results of this study concluded that the struggle of the petitioners to realize the legalization of marijuana ran aground in the constitutional court (MK).